2010
DOI: 10.1021/jo101096n
|View full text |Cite
|
Sign up to set email alerts
|

Dialkynyl Carbene Derivatives: Generation and Characterization of Triplet tert-Butylpentadiynylidene (t-Bu−C≡C−C̈−C≡C−H) and Dimethylpentadiynylidene (Me−C≡C−C̈−C≡C−Me)

Abstract: Triplet carbenes t-butylpentadiynylidene (t-BuC(5)H, 1a) and dimethylpentadiynylidene (MeC(5)Me, 1b) have been produced photochemically from their corresponding diazo compound precursors and studied spectroscopically in cryogenic matrices (N(2) or Ar) at 10 K. The infrared, electronic absorption, and electron paramagnetic resonance spectra of these species exhibit numerous similarities to the spectra of pentadiynylidene (HC(5)H) and methylpentadiynylidene (MeC(5)H) recorded previously. EPR spectra yield zero-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…In contrast, n = 5 carbon chains have so far been investigated predominately in low temperature matrices. Infrared, UV/vis and EPR spectra in Ar or N 2 matrix are available for 1 , 2 , and in part for 3 . While propargylene favors a slightly bent geometry with C 2 symmetry, a linear geometry with D ∞ h symmetry was found for 1 , as confirmed by coupled cluster calculations . In a valence bond picture, pentadiynylidene can be described by two resonance structures (see Figure ), one corresponding to a 1,5-biradical and a second dominating one to a diethynylcarbene.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, n = 5 carbon chains have so far been investigated predominately in low temperature matrices. Infrared, UV/vis and EPR spectra in Ar or N 2 matrix are available for 1 , 2 , and in part for 3 . While propargylene favors a slightly bent geometry with C 2 symmetry, a linear geometry with D ∞ h symmetry was found for 1 , as confirmed by coupled cluster calculations . In a valence bond picture, pentadiynylidene can be described by two resonance structures (see Figure ), one corresponding to a 1,5-biradical and a second dominating one to a diethynylcarbene.…”
Section: Introductionmentioning
confidence: 75%
“…In the pyrolysis of 6 a small peak appears at m/z = 91. It originates from the 13 C isotope of m/z = 90 as evident from the relative peak intensities in the mass spectrum and not from a H-atom addition product. b. Photoionization of precursors 4, 5 and 6.…”
Section: Methodsmentioning
confidence: 97%
“…28 From our studies, we suspect that the bond length behavior could be related the a π bond resonance between carbon atoms. One example of the resonance effect in linear chains is the case of tert-butylpentadiynylidene and dimethylpentadiynylidene, 29 where computational and experimental studies indicated this behavior. In agreement with other works, 28 our results suggest that the bonds present a resonance effect.…”
Section: The Mpb Description Of Nw Structurementioning
confidence: 99%
“…When an O 2 -doped matrix was used, carbonyl oxides derived predominantly from attack at C 3 were formed, while both t-BuC5H and MeC5Me rearrange photochemically upon UV irradiation. 139 By photolysis of the diazidopyridines, 4-amino-2,6-diazido-3,5-dichloropyridine and 6-amino2,4-diazido-1,3,5-triazine, triplet-triplet nitrene pairs were produced, yielding ESR spectra characteristic of the quintet spin state. The high-spin state (S = 2) results from the exchange interaction between two triplet molecules with the zero-field splitting parameters |D| = 1.0280 cm À1 and |E| = 0.0038 cm À1 and the angle between two C-N nitrene bonds y = 1331.…”
Section: Organic Radicalsmentioning
confidence: 99%